2019
DOI: 10.21873/anticanres.13640
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia as Prognostic Factor in Lung Cancer Patients: A Systematic Review and Meta-analysis

Abstract: Background/Aim: Sarcopenia describes the loss of skeletal muscle mass. While this condition is associated with a high mortality in cancer patients, its influence on survival is still underestimated. Patients and Methods: A systematic review for articles was performed using the PubMed database, Cochrane Library, Biomed Central, Science Direct and by manual search. We used data of overall survival in sarcopenic patients for assessing the death risk. We extracted hazard ratio estimates from univariate and multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 25 publications
4
56
0
5
Order By: Relevance
“…The subgroup analyses in our meta-analysis according to cancer type yielded results largely consistent results with previous meta-analyses. Previous literature have identified significant associations in patients with lung cancer [ 10 ], head and neck cancer [ 11 , 18 ], GI cancer [ 9 , 19 , 20 ], liver cancer [ 9 , 21 , 22 ], pancreatic cancer [ 23 ], and urinary tract cancer [ 24 ], with largely consistent effect sized identified in the current meta-analysis. However, other recently published meta-analyses by Zhang et al [ 25 ], Ubachs et al [ 26 ], and Jia et al [ 27 ] have identified a significant association between sarcopenia and survival in breast cancer, ovarian cancer, and hematological malignancies, respectively, contrary to insignificant association identified in the current meta-analysis.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The subgroup analyses in our meta-analysis according to cancer type yielded results largely consistent results with previous meta-analyses. Previous literature have identified significant associations in patients with lung cancer [ 10 ], head and neck cancer [ 11 , 18 ], GI cancer [ 9 , 19 , 20 ], liver cancer [ 9 , 21 , 22 ], pancreatic cancer [ 23 ], and urinary tract cancer [ 24 ], with largely consistent effect sized identified in the current meta-analysis. However, other recently published meta-analyses by Zhang et al [ 25 ], Ubachs et al [ 26 ], and Jia et al [ 27 ] have identified a significant association between sarcopenia and survival in breast cancer, ovarian cancer, and hematological malignancies, respectively, contrary to insignificant association identified in the current meta-analysis.…”
Section: Discussionsupporting
confidence: 80%
“…Previous meta-analyses have suggested that sarcopenia is associated with a higher mortality in cancer patients [ [9] , [10] , [11] ]. However, these meta-analyses focussed on certain type(s) of cancer, and whether these results could be generalized to a wider spectrum of cancer types remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Our subgroup results found that when considering the reasons for admission, critically ill patients with sarcopenia have an increased risk of mortality, profoundly con rming that sarcopenia could be a prognostic factor in critical illness. Our ndings are in line with previous research, which has found that older adults with sarcopenia are at increased risk of mortality in other settings, such as the community 36 , nursing homes 43 , or in an oncology setting [44][45][46] . According to published studies, the main reason explaining the relationship between sarcopenia and mortality is lower muscle mass, which has been con rmed as a strong predictor for an increased risk of death 31,47 .…”
Section: Discussionsupporting
confidence: 92%
“…Previous meta-analyses evaluated the impact of lean mass on mortality in a particular population, such as people awaiting liver transplantation [ 7 , 8 ], or people with liver cirrhosis [ 10 ], tumors [ [11] , [12] , [13] , [14] ], and post-operation [ [15] , [16] , [17] , [18] , [19] ]. Some studies included less validated methods, such as phase angle [ 14 ] and mid-arm muscle [ 8 ] in the meta-analysis. The risk estimates identified in these studies were largely consistent with the estimated identified in the subgroup analysis of the present meta-analysis.…”
Section: Discussionmentioning
confidence: 99%